Escherichia coli mono articular septic arthritis of shoulder joint in an elderly female - Narula, Shubhank; Kakar, Atul; Gogia, Atul; Batra, Tanvi (International Journal of Research in Orthopaedics, 2024)
Septic arthritis of the shoulder joint is a very rare entity to encounter in clinical practice. Escherichia coli (E. coli) pathogen isolation is only seen to occur in individuals with multiple comorbidities. We report a similar case of gram-negative E. coli urosepsis in a veteran female that transmitted hematogenously to the shoulder joint and how a prompt diagnosis and treatment prevented extension and damage of the joint space.